Rice Straw Eco Icebox (RSEI) - Zulkifli, Mohd Daniel (Progress in Engineering Application and Technology, 2021)
Non-biodegradable waste is material which does not decompose, decay or dissolve by natural phase which categorize such as plastic, glass, metal and another else. As non-biodegradable waste can contribute to the impact on the environmental pollution and human health. At the same time, in Malaysia is well known as a major rice producer in the economic sector produced by paddy cultivation. However, the rice straw will be burned after harvest season which produces combustion that contribute to air pollution. Therefore, in this study was the development of a biodegradable product in replacing polystyrene container namely Rice Straw Eco Icebox (RSEI) was proposed. This product was design by three combinations of agricultural waste which are rice straw with other natural components such as clay soil, corn flour and water in different ratio which were assigned as RSEI 1, 2 and 3, for first, second and third combination ratio, respectively. The combinations of rice straw, clay soil, corn flour and water mixture were tested for comparison with polystyrene with regards to their strength, water absorption, heat transfer, load capacity and combustible test. Based on the testing conducted on all three RSEI samples, water absorption and heat transfer testing showed that RSEI 1 had the best performance compared to RSEI 2 and RSEI 3 as the water absorption determined 20% and the heat transfer based on five hours of ice melting was 20.5 kJ/kg. In terms of load capacity and combustible test, RSEI 1 was found to have the similar capacity and fire retention properties as RSEI 2 and RSEI 3. However, comparison made to polystyrene found that the water absorption of polystyrene is 0% with the heat transfer of 26.2 kJ/kg. Due to the findings, and based on five hours usage this Eco icebox was found to be comparable with polystyrene purpose as a food container. The biodegradable components of RSEI make this product can be used to replace polystyrene however with some modifications to enhance the properties comparable to polystyrene in the future.